Carbon emission and environmental cost from coal production in Indonesia - Mahroini, Zahidah; Chien, Yu-Lan (Journal of Degraded and Mining Lands Management, 2024)
Indonesia primarily exports coal, with an average annual quantity of over 421 million tonnes in the past decades (2011-2020), reaching its peak at 616 million tonnes in 2019. Despite its economic benefits, coal production carries hidden costs. This research delves into using life cycle assessment (LCA) to gauge the environmental impact of coal production and estimate external cost (EC) related to Greenhouse gases (GHG) and air pollutants (AP). The study applied the benefit transfer method to make these estimations, focusing on coal mining and international transport processes. The findings revealed that over the past decades, per tonne coal mining contributed an estimated EC of $12.54-15.26 for GHG and $3,439-5,250 for AP, while transport abroad per-tonne-km coal incurred an EC of $19.98-23.94 for GHG and $19.58-23.30 for AP. Moreover, coal mining contributes to water pollution and substantial water depletion. Despite the coal production in Indonesia generating around $40 billion in revenue in 2020, the study shows that the total EC from GHG and AP is up to $2,131 billion, which is 53 times the revenue, posing serious health and ecological risks to Indonesians and exacerbating global climate change. Notably, these estimates exclude EC from water pollution (WP) and water depletion. With the global push towards ‘net zero emissions’, the coal industry as a whole faces an urgent need to curb its GHG and AP emissions from its.